COVID-19 risk perception among Indonesians in early stage of the outbreak - Ratih Oktri Nanda; Lolita Lolita; Wiwik Indayati; Ivong Rusdiyanti; Nurjannah Nurjannah; Azis Ikhsanudin; Silvia Mareti (International Journal of Public Health Science (IJPHS), 2021)
Indonesia confirmed its first coronavirus disease 19 (COVID-19) case on 2nd March 2020, when other countries have already reported several numbers in the previous month. This study aimed to explore the risk perception of Indonesians in the early stage of the COVID-19 outbreak. This cross-sectional study was conducted among 495 participants using a web-based questionnaire. Primary data were collected from 3rd to 27th March 2020 including the perceived severity, vulnerability, threat, self, and response efficacy of the participants. The results showed that the perceived threat of the outbreak in its early stage is the second highest compared to other diseases. The perceived severity among the participants was high. However, they had a low vulnerability. Those in the middle region showed a higher level of self and response efficacy. Meanwhile, people who work as private sector employee (β=0.146, p=0.004), live in the western region (β=-0.184, p=0.000), with a higher knowledge score (β=0.096, p=0.032) had a higher perceived threat. These results found those who had high knowledge, was also had higher perceived risk. The most important of these studies have determined various factors related to risk perception, thus it could be good preliminary evidence for public health authorities to arrange an effective way for epidemic control.